Molecular basis of substrate translocation through the outer membrane channel OprD of Pseudomonas aeruginosa1. Issue 37 (7th October 2015) - Samanta, Susruta; Scorciapino, Mariano Andrea; Ceccarelli, Matteo
<x xml:space="preserve">Abstract</x> The dynamics and interplay of internal and external loops create two alternative paths for the permeation of substrates through the specific outer membrane channel OprD.